Temporal Factors to evaluate trustworthiness of virtual identities - DONDIO, PIERPAOLO (IEEE, 2007)
In this paper we investigate how temporal factors (i.e. factors computed by considering only the time-distribution of interactions) can be used as an evidence of an entity?s trustworthiness. While reputation and direct experience are the two most widely used sources of trust in applications, we believe that new sources of evidence and new applications should be investigated [1]. Moreover, while these two classical techniques are based on evaluating the outcomes of interactions (direct or indirect), temporal factors are based on quantitative analysis, representing an alternative way of assessing trust. Our presumption is that, even with this limited information, temporal factors could be a plausible evidence of trust that might be aggregated with more traditional sources. After defining our formal model of four main temporal factors - activity, presence, regularity, frequency, we performed an evaluation over the Wikipedia project, considering more than 12000 users and 94000 articles. Our encouraging results show how, based solely on temporal factors, plausible trust decisions can be achieved.
Third International Workshop on the Value of Security through Collaboration, SECURECOM 2007
PUBLISHED
Keywords: Computer Science